HOW TO ENGAGE A COMMUNITY AND IMPROVE CHILDREN'S ORAL HEALTH - Andrew John Macnab; Ronald Mukisa (Proceedings of the International Conference on Applied Science and Health, 2018)
Background: Globally, gingivitis (gum inflammation) and dental caries (tooth decay) have a negative impact on the health and quality of life of children. Those from disadvantaged populations suffer disproportionally from poor oral health, yet much of the pathology and associated pain and suffering is preventable if children are taught simple and inexpensive practices that can improve their oral health. The World Health Organization (WHO) has called for more programs to improve children’s oral healthworldwide. Aims: To summarize how readily implemented school-based programs can provide knowledge and teach health practices that promote behaviors that can enable children to improve their oral health through better hygiene and a reduced incidence of gum disease and caries. Results: The WHO Health Promoting School (HPS) program model is well suited to address poor oral health. The model begins with community dialogue to establish understanding of the cause, adverse effects and approaches to prevention. Next teachers are helped to establish, sustain and evaluate an intervention in the local school. Intervention is based on the two core components of WHO HPS programs; first, teachers add health-related curriculum and visual aid production to classroom activities, and second, opportunities are added for children to participate in health-related practices while at school, for example tooth brushing or tooth stick sessions to clean their teeth after the lunch break. Conclusions: Poor oral health is an example of a worldwide public health issue of central importance to children where school-based intervention has been shown to have benefits, through changes in behaviors achieved through teaching a combination of simple factual knowledge and inexpensive health practices.